7.
(2b^2+7b^2+b)+(2b^2-4b-12)
(9b^2+b)+(2b^2-4b-12)
9b^2+b+2b^2-4b-12
11b^2+b-4b-12
11b^2-3b-12
8.
(7g^3+4g-1)+(2g^2-6g+2)
7g^3+4g-1+2g^2-6g+2
7g^3-2g-1+2g^2+2
7g^3-2g+1+2g^2
7g^3+2g^2-2g+1
Hope this helps!
Answer:
x = 45
Step-by-step explanation:
Re-order terms so constants are on the left
15 * x/9 - 42 =28
Combine multiplied terms into a single fraction
15x/9 - 42 = 28
Cancel terms that are in both the numerator and denominator
5x/3 - 42 = 28
Answer:
1 1/2
Hope that helps!
Step-by-step explanation: